2023
DOI: 10.3866/pku.whxb202212060
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Dry Reforming of Methane via Photothermocatalysis

Abstract: During the development of traditional industries, large amounts of greenhouse gases have been emitted due to the increasing consumption of fossil energy. CH4 and CO2 account for more than 98% of greenhouse gas emissions, and the conversion of CH4 and CO2 into high value-added chemicals has attracted extensive attention from both industry and academia. Dry reforming of methane (DRM) can co-convert CH4 and CO2 into syngas, which can be further converted into various value-added fuels and chemicals through Fische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The harsh reaction conditions also lead to rapid deactivation due to catalyst sintering and carbon deposition. [30,[42][43][44] In Ruitao contrast, photocatalytic methane reforming can occur under mild reaction conditions, which not only effectively reduces energy consumption but also avoids the catalyst deactivation. In recent years, significant progress has been achieved in catalyst development for photocatalytic reforming of CH 4 as summarized in Table 1.…”
Section: Photocatalytic Reforming Of Methane To Syngasmentioning
confidence: 99%
“…The harsh reaction conditions also lead to rapid deactivation due to catalyst sintering and carbon deposition. [30,[42][43][44] In Ruitao contrast, photocatalytic methane reforming can occur under mild reaction conditions, which not only effectively reduces energy consumption but also avoids the catalyst deactivation. In recent years, significant progress has been achieved in catalyst development for photocatalytic reforming of CH 4 as summarized in Table 1.…”
Section: Photocatalytic Reforming Of Methane To Syngasmentioning
confidence: 99%
“…At present, various methods, including plasma, combustion, and catalytic hydrolysis, have been developed for the decomposition methods of CF 4 . Among them, catalytic hydrolysis is regarded as a promising method owing to its capability of high decomposition efficiency and large gas flux. Al-based materials with abundant acidic sites are the most used catalysts in decomposition of CF 4 . Song et al reported that the more the Lewis acid sites on the surface of Al-based catalysts, the stronger the ability to decompose CF 4 . Zhang et al found that the strong Lewis acid site of unsaturated tricoordinated Al (Al III ) was the main active site for CF 4 decomposition, indicating that more Al III active sites represent higher CF 4 decomposition activity.…”
Section: Introductionmentioning
confidence: 99%